Family cohesion and time of hospitalization in patients with mental disorders in a hospital in Lambayeque, Peru: Cohesión familiar y tiempo de internamiento en pacientes con trastornos mentales de un hospital de Lambayeque, Perú - Monsalve Mera, Alain Eduard (2021)
Mental disorders represent about 22% of the total burden of disease, and family support plays an important role in the length of hospitalization time in these patients. We described the family cohesion and the time of hospitalization in patients of the psychiatric service of the Almanzor Aguinaga Asenjo National Hospital (H.N.A.A.A) during 2019. This is a cross-sectional descriptive census-type study, in which a questionnaire of 11 questions on family cohesion was applied. Sociodemographic and clinical data were collected through a data collection form. 60 patients were surveyed, the median age was 50 years, the most frequent diagnosis was schizophrenia; most are female, not working and are single. The median length of detention was 12.5 days. Those who respond positively to questions tend to stay longer